The influence of the transducer bandwidth on the efficient Golay codes compression - Ihor Trots; Andrzej Nowicki; Wojciech Secomski; Ryszard Tymkiewicz (Archives of Acoustics)
The maximization of penetration depth with concurrent retaining or enhancement of image resolution constitutes one of the time invariant challenges in ultrasound imaging. To solve this problem a pulse compression technique employing long coded sequences is now under intensive investigation and in fact some of the corresponding techniques were already implemented in commercial scanning machines. This paper investigates the influence of the effective bandwidth of the transducer on the behaviour of the encoding/compression technique and its potential influence on the axial resolution. We have investigated two different bits lengths – one and two periods – in the Golay sequences resulting in substantial difference of the bandwidth of the transmitted sequences. Three transducers with different fractional bandwidths were used in the experiments: 6 MHz focused transducer with 25% fractional bandwidth, 4.4 MHz flat transducer with 58% fractional bandwidth and 6 MHz flat, composite transducer with 80% fractional bandwidth. The experimental results are clearly showing that the elongation of the Golay single bit length (two cycles in our case) compensates for the limited transducer bandwidth. For 25% bandwidth peak-to-peak echo increased by 1.89 times; for 58% bandwidth peak-to-peak echo amplitude increased by 1.62 times, and for 80% bandwidth peak-to-peak echo increased by 1.47 times.